Enhancing Students’ Critical Thinking Skills through Problem-Based Learning and Diorama Media: A Study at SD 3 Jurang - Ririn Anggraini; Siti Masfuah; Lovika Ardana Riswari (LPPM Universitas PGRI Semarang, 2025)
This research is motivated by monotonous learning using conventional models such as lectures and limited media usage, which can result in a lack of students' critical thinking skills. The objective of this research is to enhance students' critical thinking skills in IPAS material by using the Problem Based Learning model and diorama media. The Classroom Action Research method consists of 2 cycles with 2 meetings. The research subjects in the fifth grade of SDN 3 Jurang for the 2023/2024 academic year consist of 17 students, with 8 male students and 9 female students. The data analysis techniques used are quantitative and qualitative. Qualitative data were obtained through performance observation sheets, while quantitative data were obtained through evaluation tests. The results of the study showed significant achievements, with the assessment of students' critical thinking skills using the Problem Based Learning model and diorama media obtaining a score of 61.6 with a completion percentage of 35.3% in Cycle I, increasing to 80.9 with a completion percentage of 82.4% in Cycle II which means it is included in the Very Critical category. This study should allow teachers to apply the Problem Based Learning model and diorama media more interestingly through practice and group discussions, through this model students can improve critical thinking patterns in science learning.